PECULIARITIES OF PSYCHOPHYSIOLOGICAL STATUS OF BIOLOGICAL AND MEDICAL SECOND-YEAR STUDENTS - Gorkavaya, Anna Yurevna; Sidorova, Olga Nikolaevna; Kuznetsova, Irina Aleksandrovna (V mire naučnych otkrytij, 2016)
The paper deals with psychophysiological features of biological and medical second-year students. Parameters of physical development and cardiovascular system were measured in 88 medical students (52 men and 36 women) and 89 biological students (36 men and 53 women). Peculiarities of psychoemotional status of the women, studying both in biological and medical universities, have been examined with the help of the standard methods. Underweight was detected in 1/3 men studying in medical university and in 1/4 men studying in biological university, in 1/5 women studying in both universities. In more than a half of cases, reduction of lung capacity and muscle strength of the hand was found in biological and medical students of both sexes. Cardiohemodinamic markers in all participants met the normative standards. Balanced state of intro-extroversive attitude, medium level of neuroticism and personal anxiety, hyperthymic type of character accentuation were revealed in most cases in women. At the same time, elevated levels of reactive anxiety and high risk of coronary-prone behavior was higher in women studying in medical university as compared to biological students. The paper discusses possible causes of mentioned specific differences and degree of physiological adequateness of the psychoemotional pattern in women studying in medical university.